Horizontal Management at Russian University: Current Trend or Urgent Need? - S. V. Butsyk (Высшее образование в России)
The article addresses an actual problem of using horizontal methods in university management in Russia. Two organizational processes are analyzed, which are relatively new for Russian universities, which came, in many respects, from the Western education system: postgraduate training (Master’s programs) and training of foreign citizens in the preparatory departments (programs in Russian). These two processes, in the opinion of the author, over the past few years could become a platform for approbation of new modern approaches to management in Russian universities and institutes. The sample study included three federal universities located in one of the regions of Russia (classical university, university for humanities and pedagogy, and institute of culture and arts). It is shown that large educational organizations, as a rule, try to integrate new processes in the traditional (vertical) management structure. The basic prerequisites for implementing horizontal ma- nagement in the institutes of culture, were mainly economic, not organizational or innovative. At the same time, the practical experience of using mixed (horizontal-vertical) management structures in the Chelyabinsk State Institute of Culture and Arts showed positive results both in terms of economic and educational-organizational indicators.